How was it done? : the story of human ingenuity through the ages - Gould, David, 1962 August 10-; Reader's Digest Association (Pleasantville, N.Y. : Reader's Digest, 1998)
Presents the inside stories behind over 250 of humanity's most significant achievements, from prehistoric times through the late twentieth century; and includes related anecdotes, artifacts, and illustrations.
At head of title: Reader's Digest.
Includes index.
Young Adult
Keywords: Technology -- History; Technology -- History